EFEKTIVITAS RESES ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN BENGKALIS PERIODE 2009-2014 (Studi Dapil I Kecamatan Bantan, Kecamatan Bengkalis, Kecamatan Rupat, dan Kecamatan Rupat Utara) - Qory Kumala Putri; M.Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Recess is a two-way communication between the legislative work with the public through periodic visits. While the recess is a time of activity Legislative Council (DPRD) outside activities during the trial and outside the parliament building. Carried recess for three (3) times a year or 14 times a recess in the period of 5 years term Legislative Council (DPRD) .The purpose of this study was to determine the implementation of the recess Members of Parliament (DPRD) Bengkalis 2009-2014 period, especially in the first electoral district san to determine the factors supporting and inhibiting the implementation of recess Members of Parliament (DPRD) Bengkalis Period 2009-2014 , especially in the electoral district I. This research was conducted in villages in the District Bantan, District Bengkalis, District Rupat, and District of North Rupat Bengkalis Riau Province. This type of research is a descriptive writer is trying to portray the facts with express and describe the symptoms to fully studied in the research aspect. So this study sought to discover phenomena that occur in the field. While the methods I use in this study is qualitative and quantitative methode. Sampling method in the study ni is purposive sampling method . While the data collection methods used were interviews, questionnaires, and documentation.The conclusion of this research is undertaken in recess Bengkalis’s members were effective in absorbing the aspirations of the people in the constituency. It can be seen from the results of measurements by the author using liqueur scale, where the number of scores obtained from the study were 957 or 68.36%, of which 100% is expected. Thus, based on data obtained from 8 and 35 question questionnaire respondents, the average percentage of 68.36% or 957 to be effective in the category, where the effective percentage is 61% -80%. It can be seen that the factors supporting the implementation of local legislators recess Bengkalis especially on the selection of author, namely: the Fund recess provided and Public participation. Meanwhile, the results of interviews conducted by the author with the respondent factors inhibiting the implementation of local legislators recess Bengkalis especially on the selection of I, namely: opinion Expenditure Budget (budget) is limited, the limited meeting time, lack of facilities Bengkalis parliament, and parliament Member flurry Bengkalis.Key word : Recess, Members of Parliament, Bengkalis Regency.